2/3.5+4/5.9+8/9.17
\(\dfrac{4}{3.5}\) + \(\dfrac{8}{5.9}\) + \(\dfrac{12}{9.15}\)+.......+
\(\dfrac{32}{x(x+16)}\) = \(\dfrac{16}{15}\)
\(\dfrac{32}{x(x+16)}\) = \(\dfrac{16}{15}\)
\(\dfrac{HeLp}{me}\) \(\dfrac{nguyễn}{đức}{Trí}\)
\(\dfrac{4}{3.5}+\dfrac{8}{5.9}+\dfrac{12}{9.15}+...+\dfrac{32}{x\left(x+16\right)}=\dfrac{16}{15}\)
\(2.\left(\dfrac{2}{3.5}+\dfrac{4}{5.9}+\dfrac{6}{9.15}+..+\dfrac{16}{X.\left(X+16\right)}\right)=\dfrac{16}{15}\)
\(\dfrac{1}{3}-\dfrac{1}{5}+\dfrac{1}{5}-\dfrac{1}{9}+\dfrac{1}{9}-\dfrac{1}{15}+...+\dfrac{1}{X}-\dfrac{1}{X+16}=\dfrac{8}{15}\)
\(\dfrac{1}{X+16}=\dfrac{1}{3}-\dfrac{8}{15}\)
\(\dfrac{1}{X+16}=\dfrac{-1}{5}\)
\(X+16=-5\)
\(X=-21\)
Tìm số tự nhiên biết: \(\frac{4}{3.5}+\frac{8}{5.9}+\frac{12}{9.15}+...+\frac{32}{n.\left(n+16\right)}=\frac{16}{25}\)
\(\frac{4}{3.5}+\frac{8}{5.9}+\frac{12}{9.15}+...+\frac{32}{n\left(n+16\right)}=\frac{16}{25}\)
\(2\left(\frac{1}{3}-\frac{1}{5}\right)+2\left(\frac{1}{5}-\frac{1}{9}\right)+2\left(\frac{1}{9}-\frac{1}{15}\right)+...+2\left(\frac{1}{n}-\frac{1}{n+16}\right)=\frac{16}{25}\)
\(2\left(\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{9}+\frac{1}{9}-\frac{1}{15}+...+\frac{1}{n}-\frac{1}{n+16}\right)=\frac{16}{25}\)
\(2\left(\frac{1}{3}-\frac{1}{n+16}\right)=\frac{16}{25}\)
\(\frac{1}{3}-\frac{1}{n+16}=\frac{8}{25}\)
\(\frac{1}{n+16}=\frac{1}{75}\)
\(\Rightarrow n+16=75\)
\(\Rightarrow n=59\)
bạn Thanh Tùng DZ mình vẫn chưa hiểu tại sao \(\dfrac{8}{5.9}\) = 2.(\(\dfrac{1}{5}\) - \(\dfrac{1}{9}\))
\(M=\frac{1}{3.4}+\frac{7}{3.4}+\frac{2}{3.5}+\frac{14}{5.9}-\frac{4}{9.13}=?\)
\(M=\frac{1}{3.4}+\frac{7}{3.4}+\frac{2}{3.5}+\frac{14}{5.9}-\frac{4}{9.13}=\frac{8}{3.4}+\frac{2}{3.5}+\frac{2}{9}\left(\frac{7}{5}-\frac{2}{13}\right)\)
=> \(M=\frac{2}{3}+\frac{2}{3.5}+\frac{2}{9}.\frac{81}{5.13}=\frac{2}{3}\left(1+\frac{1}{5}\right)+\frac{18}{5.13}\)
=> \(M=\frac{2}{3}.\frac{6}{5}+\frac{18}{5.13}=\frac{4}{5}+\frac{18}{5.13}=\frac{2}{5}\left(2+\frac{9}{13}\right)=\frac{2}{5}.\frac{35}{13}\)
=> \(M=\frac{14}{13}\)
-8/15.3/7.15/-8.14=..... 17/27.13/9-4/9.17/27=.......
\(\dfrac{-8}{15}.\dfrac{3}{7}.\dfrac{15}{-8}.14=\left(\dfrac{-8}{15}.\dfrac{15}{-8}\right).\left(\dfrac{3}{7}.14\right)=1.6=6\)
\(\dfrac{17}{27}.\dfrac{13}{9}-\dfrac{4}{9}.\dfrac{17}{27}=\dfrac{17}{27}.\left(\dfrac{13}{9}-\dfrac{4}{9}\right)=\dfrac{17}{27}.1=\dfrac{17}{27}\)
\(\left(\frac{8}{1.9}+\frac{8}{9.17}+\frac{8}{17.25}+.....+\frac{8}{49.57}\right)+2.\left(x-1\right)=\frac{2x+7}{3}+\frac{5x-8}{4}\)
Ta có: \(\left(\frac{8}{1.9}+\frac{8}{9.17}+\frac{8}{17.25}+...+\frac{8}{49.57}\right)+2\left(x-1\right)=\frac{2x+7}{3}+\frac{5x-8}{4}\)
\(\Leftrightarrow1-\frac{1}{9}+\frac{1}{9}-\frac{1}{17}+\frac{1}{17}-\frac{1}{25}+....+\frac{1}{49}-\frac{1}{57}+2x-2=\frac{8x+28+15x-24}{12}\)
\(\Leftrightarrow1-\frac{1}{57}+2x-2=\frac{23x+4}{12}\)
\(\Leftrightarrow2x-\frac{58}{57}=\frac{23x+4}{12}\)
\(\Leftrightarrow24x-\frac{232}{19}=23x+4\)
\(\Leftrightarrow x=\frac{308}{19}\)
Cho E=2^15.0,5^5+3.2^10/2^11.2^3-2^15:2^3 Cho F=2.6^7+6^8/2^5.9^4-2.3^7+3^8 Cho G=4^5.9^4-2.6^9/2^10.3^8+6^8.20
tính
A= 5/1.3+5/3.5+5/5.7+.....+5/99.101
tìm x
x+4/5.9+4/9.13+4/13.17+...+4/41.45=-37/45
bài 1
\(2A=\left(\frac{5}{1\cdot3}+\frac{5}{3\cdot5}+...+\frac{5}{99\cdot101}\right)\cdot2\)
\(=5\left(\frac{2}{1\cdot3}+\frac{2}{3\cdot5}+...+\frac{2}{99\cdot101}\right)\)
\(=5\left(1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+...+\frac{1}{99}-\frac{1}{101}\right)\)
\(=5\left(1-\frac{1}{101}\right)\)
\(=5\cdot\frac{100}{101}\)
\(=\frac{500}{101}\Rightarrow A=\frac{500}{101}:2=\frac{250}{101}\)
bài 2:
\(x+\frac{1}{5}-\frac{1}{9}+\frac{1}{9}-\frac{1}{13}+...+\frac{1}{41}-\frac{1}{45}=-\frac{37}{45}\)
\(x+\left(\frac{1}{5}-\frac{1}{45}\right)=-\frac{37}{45}\)
\(x+\frac{8}{45}=-\frac{37}{45}\)
\(x=-\frac{37}{45}-\frac{8}{45}\)
\(x=\frac{-45}{45}=-1\)
Tìm x:
\(\frac{8}{1.9}+\frac{8}{9.17}+...+\frac{8}{49.57}+\frac{58}{57}+2x-2=2x+\frac{7}{3}+5x-\frac{8}{4}\)
Ta có: \(\frac{8}{1.9}+\frac{8}{9.17}+...+\frac{8}{49.57}=1-\frac{1}{9}+\frac{1}{9}-\frac{1}{17}+...+\frac{1}{49}-\frac{1}{57}=1-\frac{1}{57}=\frac{56}{57}\)
Vậy: 56/57 + 58/57 + 2x - 2 = 2x + 7/3 + 5x - 8/4
2 + 2x - 2 = 2x + 7/3 + 5x - 8/4
2x = 2x + 7/3 + 5x - 8/4
=> 7/3 + 5x - 8/4 = 0
1/3 + 5x = 0
=> 5x = -1/3
=> x = -1/3 : 5=-1/15
A, m= 4/1.3+4/3.5+4/5.7+....+4/2013.2015
b,S=2/5.9+2/9.13+2/13.17+....+2/97.101
c,A=1/5.6+1/6.7+1/7.8+......+1/24.25
d,B=2/1.3+2/3.5+2/5.7+....+2/99.101
e,C=52/1.6+52/6.11+52/11.16+52/16.21+52/21.26+52/26.31